Patients' Perception of Anaesthesia, the Anaesthetist and Experience of Anaesthesia Care - Emmanuel EA; Fatungase OM; Shoyemi RO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: The anaesthetist is a health care professional, but misconceptions about her identity and roles influence patient satisfaction, a unique clinical endpoint. Objective: To determine patients' perception of the anaesthetist and their satisfaction with perioperative anaesthesia care. Methods: This prospective study recruited adult patients scheduled for elective surgeries in a Nigerian tertiary health facility. A structured questionnaire was administered during the pre-anaesthetic visit, before the administration of anaesthesia and 24 hours post-operative to elicit information on socio-demographics, type of surgery, patient's perception of anaesthetist as a specialist, previous and index anaesthesia experience, and patient's satisfaction from the perioperative anaesthesia care. Results: One hundred (23 males and 77 females) adult patients with a mean age of 42.17±12.87 years were recruited for elective surgeries in various surgical specialities. Seventy-eight per cent were familiar with the roles of anaesthetists, but those with previous exposure to anaesthesia and a higher educational status showed better knowledge. Most participants (89%) realised that the anaesthetist was a qualified doctor. Still, when probed further, it was discovered that only 42% could anticipate that the anaesthetist was in charge of the operating theatre. A majority (73%) were unaware that the anaesthetist works outside the operating theatre. The participants were very satisfied (68%) or satisfied (32%) with the post-operative assessment of perioperative anaesthesia care. Conclusion: Most patients scheduled for elective surgeries were familiar with anaesthetist roles and identity but were unaware of her role outside the operating theatre.